Human Capital in the Formation of Efficiency of Enterprises Activity - Hryvkivska, Svіtlana; Polishchuk, Nataliia; Salkova, Iryna; Kucher, Lesia (European Journal of Sustainable Development, 2019)
The purpose of the article is to determine the role of human capital in the functioning of machine-building enterprises, based on the peculiarities of the formation of labor costs for hired workers in relation to the dynamics of capital expenditures (fixed assets) in order to increase revenue (revenues) from sales of products. The method of correlation-regression analysis has been used, which has revealed the high density of communication, to construct the equation of the dependence of labor costs and capital expenditures (fixed assets) on income (revenue) from sales of products. Using the method of analysis of the functioning environment, according to the machine-building enterprises of the region, the coefficients of covering income (revenue) from the sale of capital expenditures (fixed assets) and labor costs for hired workers, formed the ability to find the indicators of capital expenditure (fixed assets). according to given economic entities the possibility of increasing the income (revenue) from sales of products. The directions of strengthening the development of human capital, in particular, by increasing the cost of capital (fixed assets) of machine-building enterprises in the region, which will increase their profitability, are revealed. Key words: human capital, physical capital (fixed assets), income (revenue) from sales of products, enterprises, correlation-regression analysis, analysis of the functioning environment.